2012
DOI: 10.1007/82_2012_232
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances on NOTCH Signaling in T-ALL

Abstract: NOTCH1 receptor signaling plays a central role in T-cell lineage specification and in supporting the growth and proliferation of immature T-cell progenitors in the thymus during lymphoid development. In T-cell acute lymphoblastic leukemia (T-ALL), a tumor resulting from the malignant transformation of T-cell progenitors, aberrant and constitutively active NOTCH1 signaling triggered by activating mutations in the NOTCH1 gene contributes to oncogenic transformation and is a hallmark of this disease. Most notably… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
40
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 108 publications
4
40
0
Order By: Relevance
“…MAML also recruits proteins leading to NICD degradation (3). The activating Notch1 mutations in T-ALL lead to either ligand-independent ADAM metalloprotease cleavage and/or diminished NICD degradation (4).…”
mentioning
confidence: 99%
“…MAML also recruits proteins leading to NICD degradation (3). The activating Notch1 mutations in T-ALL lead to either ligand-independent ADAM metalloprotease cleavage and/or diminished NICD degradation (4).…”
mentioning
confidence: 99%
“…NOTCH1 was first discovered as a partner gene in the t(7;9)(q34;q34) chromosomal translocation 16 and was later implicated in the pathogenesis of up to 60% of T-ALL, harboring activating mutations, involving negative regulatory domains responsible for the control of initiation and termination of NOTCH signaling. 17,18 Additionally, it was found that mutations in the FBXW7 gene are present in 15% of T-ALL cases, and these interfere with the proteasomal degradation of activated NOTCH1 protein. [18][19][20][21] In addition to NOTCH1 mutations, T-ALLs frequently show T-cell receptor gene chromosomal translocations, resulting in aberrant expression of transcription factor oncogenes, such as TAL1, LMO1, LMO2, TLX1, and TLX3.…”
Section: Biology and Pathogenesismentioning
confidence: 99%
“…17,18 Additionally, it was found that mutations in the FBXW7 gene are present in 15% of T-ALL cases, and these interfere with the proteasomal degradation of activated NOTCH1 protein. [18][19][20][21] In addition to NOTCH1 mutations, T-ALLs frequently show T-cell receptor gene chromosomal translocations, resulting in aberrant expression of transcription factor oncogenes, such as TAL1, LMO1, LMO2, TLX1, and TLX3. 15 Furthermore, mutations in the IL7R, JAK1, and JAK3 genes activate the IL7R/ JAK-STAT pathway, and loss of the PTEN tumor suppressor gene drives aberrant phosphatidylinositol 3-kinase (PI3K)-AKT signaling.…”
Section: Biology and Pathogenesismentioning
confidence: 99%
“…With all the studies linking aberrant Notch1 signalling effectively to the pathogenesis of T-ALL, it makes a promising therapeutic target towards T-ALL treatment (Radtke et al 2005;Palomero & Ferrando 2009). Small molecule inhibitors of γ-secretase (GSIs) capable of blocking Notch1 activation have prompted clinical trials to test their effectiveness against T-ALL ( Tzoneva & Ferrando 2012). Initial studies on human T-ALL cell lines harbouring activating mutations in Notch1 treated with GSIs confirms that inhibition of Notch signalling arrests cells at G0/G1 phase (Palomero et al 2006;Lewis et al 2007;Rao et al 2009).…”
Section: Notch Pathwaymentioning
confidence: 99%